Analysis of Factors Influencing Behavioral Intention to Use Cloud-Based Academic Information System Using Extended Technology Acceptance Model (TAM) and Expectation-Confirmation Model (ECM) - Wandira, Raju; Fauzi, Ahmad; Nurahim, Faisal (Journal of Information Systems Engineering and Business Intelligence, 2024)
Background: Technology Acceptance Model (TAM) and Expectation-Confirmation Model (ECM) integration model are commonly used to analyze the intention to use technology in education. Moreover, the ease of implementation causes various external factors influencing technology acceptance to continue growing. However, limited research focuses on the use of TAM and ECM in the acceptance of cloud-based academic system. Objective: This research aims to identify factors influencing user perceptions of cloud-based academic information system and the relationships among different factors. Methods: The research integrated Extended TAM and ECM, subsequently processing data obtained from 261 respondents using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The perceptions proposed included Facilitating Condition (FC), Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Confirmation (CM), Satisfaction (SF), and Behavioral Intention to Use (BIU). Results: Based on the data processing carried out, the results were PEOU against BIU (H1, êžµ=0.256, p=0.001), PU against BIU (H2, êžµ=0.200, p=0.007), and SF against BIU (H3, êžµ=0.499, p= 0.000). Furthermore, it also comprised FC against PEOU (H4, êžµ=0.839, p=0.000), PU (H5, êžµ=0.849, p=0.000) and SF (H6, êžµ=0.294, p=0.000), as well as CM against SF (H7, êžµ=0.358, p=0.000) and PU against SF (H8, êžµ=0.325, p=0.000). These results showed that each proposed construct significantly influenced behavioral intentions to use cloud-based academic information system. Conclusion: The results showed that each factor proposed in the construct significantly influenced user intentions to use cloud-based academic system. Consequently, the most influential drivers in using cloud-based academic system were SF, PU, PEOU, and FC. Keywords: Acceptance, Behavioral Intention, Cloud-Based Academic System, Expectation